Proteasome Inhibitor MG132 Enhances Cisplatin-Induced Apoptosis in Osteosarcoma Cells and Inhibits Tumor Growth - Sun, Farui (Oncol Res, 2018)
Although cisplatin has been shown to be an integral part of chemotherapy regimen in osteosarcoma (OS) treatment, toxicity issues and chemoresistance have hindered therapeutic development for OS. Exploring novel combination therapy methods is needed to circumvent the limitations of cisplatin alone. The proteasome inhibitor MG132 has shown antitumor effects in many solid tumors. However, little is known about its effects in combination with cisplatin in OS cells. In this study, we examined the effects of MG132 in combination with cisplatin in human OS cells (MG-63 and HOS). MG132 and cisplatin were applied to OS cells, respectively or jointly. The results demonstrated that MG132 markedly inhibited cell viability in a dose- and time-dependent manner, whereas viability of osteoblast cells was not affected, suggesting a selective toxicity of MG132 to cancerous cells. Mechanistically, MG132 arrested cells in the G(2)/M phase in association with increased p21(waf1) and induced cell apoptosis, which was accompanied by cleaved PARP. In addition to its apoptotic effect alone, MG132 significantly enhanced cisplatin-induced apoptosis in OS cells. Furthermore, cell viability of the combined application of 10 μM MG132 and 5 μg/ml cisplatin was markedly inhibited compared to that of the individual application. These events were accompanied by the downregulation of NF-κB, mitochondrial antiapoptotic protein Bcl-xL, and PI3K/Akt, which play a key role in cell survival. Finally, combination treatment of MG132 and cisplatin showed more antiproliferative effect than the single treatment in OS xenograft models. In summary, we concluded that MG132 interacted synergistically with cisplatin, which raised the possibility that combining the two drugs may represent a novel strategy in OS.